(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The author critically elaborates the jurisdiction of the new Probation Service as regulated within the provisions of the newly enacted Law on Probation in Republic of Macedonia. He states that the Macedonian legislator has omitted to regulate one very important part of the Probation service’s jurisdiction, such as the implementation of the measures for providing the defendant’s presence during the criminal procedure. The author stresses the fact that in one broader European sense, the Probation Services has imminent jurisdiction regarding the proper implementation of these measures, as ordered by the courts. Through this jurisdiction the probation service is serving to the court as Pre-trial service. In order to overcome this situation, author initially examines the connection between these measures and the Probation service and in addition provides specific suggestions for further improvement of Law on Probation provisions’.